METODE PEMBELAJARAN TAJWīD DIDAYAH JABAL NUR KECAMATAN DEWANTARA KABUPATEN ACEH UTARA - Rizki Yullah (Jurnal Ilmiah Didaktika, 2015)
Learning to read the Qur’an for santri (student of Islamic Boarding School) is an obligation. Even some Islamic Boarding School in Aceh (dayah) obliged their students to memorize it. However, based on some preliminary studies, it is found that some santri cannot read the Qur’an based on ‘ilm tajwīd . This research focused on students’ ability to read Qur’an based on Tajwīd at Dayah Jabal Nur, Bireun, Aceh, Indonesia. The results of the study show that the input process in Dayah Jabal Nur is based on class need analysis, administration, oral and written test of Qur’an. There are various methods used by teachers in teaching tajwīd at class 3 of Takhṣīṣ of Dayah Jabal Nur including lecturing method, question and answer method, demonstration method, training method, gabriel method, and memorization method. The lecturing method mostly used by teachers. The ability of teachers in the teaching of tajwīd learning at class 3 Takhṣīṣ of dayah Jabal Nur is generally classified as sufficient in the implementation of tajwīd learning. Although some of them are still employing the traditional teaching model, they are able to motivate students very well. Most of the students are also able to read the Qur'an according to tajwīd very well.